AGAMA SEBAGAI PILAR IDENTITAS SOSIAL DAN BUDAYA: KONTRIBUSI TERHADAP SOLIDARITAS, TOLERANSI, DAN PEMBENTUKAN KOMUNITAS - Miftahul Ulum (CV. Adiba Aisha Amira, 2025)
This study aims to examine the role of religion as a pillar of social and cultural identity and its contribution to solidarity, tolerance, and community building. Using a literature review method, this study examines various relevant literature to understand how religion shapes the values, norms, and character of society. The results of the study indicate that religion not only functions as a belief system but also as a primary source of inspiration in building a harmonious and civilised social order. Religion strengthens collective identity, fosters social solidarity, and promotes tolerance and harmony among people of different faiths. Additionally, religion plays a role in building inclusive communities through the reinforcement of humanistic values and solidarity. Thus, religion has a strategic contribution in creating a peaceful, tolerant, and civilised society amidst social and cultural diversity.